Proceedings of the European Physical Society Conference on High Energy Physics — PoS(EPS-HEP2017) 2017
DOI: 10.22323/1.314.0620
|View full text |Cite
|
Sign up to set email alerts
|

Production of cosmic-ray antinuclei in the Galaxy and background for dark matter searches

Abstract: Antimatter nuclei in cosmic rays (CR) represent a promising discovery channel for the indirect search of dark matter. We present astrophysical background calculations of CR antideuteron (d) and antihelium (He). These particles are produced by high-energy collisions of CR protons and nuclei with the gas nuclei of the interstellar medium. In our calculations, we also consider production and shock acceleration of antinuclei in the shells of supernova remnants (SNRs). The total flux of d and He particles is constr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In recent years there has been a growing interest in searches for cosmic-ray antiparticles with space-based and balloon-borne experiments, like BESS, PAMELA, and AMS-02 [1][2][3][4][5][6][7]. One of the motivations is that rare antiparticles act as messengers for exotic processes in the Galaxy, such as dark-matter annihilation or decay [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], which have a very low astrophysical background at kinetic energies below few GeV/nucleon. This background is generated by interactions of primary cosmic rays, like protons or α-particles, with the interstellar medium (ISM).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been a growing interest in searches for cosmic-ray antiparticles with space-based and balloon-borne experiments, like BESS, PAMELA, and AMS-02 [1][2][3][4][5][6][7]. One of the motivations is that rare antiparticles act as messengers for exotic processes in the Galaxy, such as dark-matter annihilation or decay [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], which have a very low astrophysical background at kinetic energies below few GeV/nucleon. This background is generated by interactions of primary cosmic rays, like protons or α-particles, with the interstellar medium (ISM).…”
Section: Introductionmentioning
confidence: 99%
“…The unique strength of a search for antideuterons lies in their ultra-low astrophysical background, particularly at low energies. Even taking into account the constraints from antiprotons, a variety of dark matter models predict an antideuteron flux that is orders of magnitude above the astrophysical background in the energy range below a few GeV/n [16,[31][32][33][34][35][36][37][38][39][40][41]. This is in contrast to other cosmic-ray dark matter searches, such as those using positrons or gamma-rays, which rely on small excesses on top of considerable astrophysical backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Antihelium arriving from antimatter-dominated regions of the universe is already nearly excluded [45,46]. Proposed models span a range including modified antihelium formation models [39,47], dark matter annihilation [38,41,[48][49][50], or emission from a nearby antistar [51]. Though these candidates are tentative, requiring verification or refutation with improved analysis from AMS-02 and a complementary experimental technique such as GAPS, a positive signal would be transformative, refashioning the field of cosmic-ray physics and potentially revolutionizing our understanding of Big Bang nucleosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with dark matter searches with antiprotons, which rely on small excesses on top of considerable astrophysical backgrounds, the unique strength of searches for cosmic antideuterons is their ultra-low astrophysical background [87,[106][107][108][109][110][111][112][113][114][115][116][117]. The production of antiprotons and heavier antinuclei can be strongly related.…”
Section: Future Developmentsmentioning
confidence: 99%
“…Antihelium arriving from antimatter-dominated regions of the universe is already nearly excluded. Recently proposed models included modified antihelium formation models, dark matter annihilation, or emission from nearby antistars [87,114,115,117,122,123]. Recent reviews can be found here [124,125].…”
Section: Future Developmentsmentioning
confidence: 99%